The effect of a conductive polyaniline/carbon black composite on the performance of a semiconductive layer. (1st September 2021) - Wang, Enmin; Zhang, Sheng; Wang, Ciyao; Chen, Shumei; Hao, Chuncheng; Lei, Qingquan
Abstract: In this study, conductive polyaniline (PANI) ribbons were introduced to a semiconductive layer to improve the conductivity stability of the layer during thermal expansion and enhance its ability to inhibit charge injection into the insulating layer. To maximise the effect of PANI, PANI and carbon black (CB) were preformed into a uniformly dispersed composite, which was then added to the polymer matrix of the semiconductive layer. The experimental results show that the resistivity of the semiconductive layer containing the PANI/CB composite is more stable during thermal expansion than that of the semiconductive layer only doped with CB. This is attributed to the conductive CB network being enhanced by the PANI ribbons. In addition, due to the unique conductivity mechanism and high dielectric constant of PANI, the semiconductive layer has a strong ability to inhibit space charge injection into the insulating layer.